Resepsi Masyarakat Dullah Utara terhadap Konsep Moderasi Beragama Perspektif Al-Qur’an - Rahmah Muharromah Yasin (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
This paper aims to describe how the North Dullah community's receptionof the concept of religious moderation from the perspective of the Qur'an. Thisscientific research aims to find out how the wasathiyah verses are based on theviewpoints and assessments of the community in the field. In this study, the areastudied has distinctive local wisdom, namely in the North Dullah sub-district, Tualcity, which is known as the Larvul Ngabal Customary Law and the Ain ni ainphilosophy. The method used in this research is field research with a qualitativeresearch type that produces descriptive data and uses a phenomenological approach.The results in this study are that religious moderation in the reception of the NorthDullah community is a moderate religious way, or an inclusive way of Islam or anopen religious attitude, not exchanging beliefs, respecting each other in tolerance,peace and justice. In its implementation in the North Dullah sub-district, it is adjustedto local customs, namely the customary law of Larvul Ngabal and the philosophy ofAin ni ain which is the basis. From the results of the interview, the researcher canconclude that in the legal articles of Larvul Ngabal and the philosophy of Ain ni ain itis clear that the customary law and philosophy are in accordance with Islamic Shari'alaw, especially the verses regarding moderation.